1993
DOI: 10.1128/jvi.67.8.4785-4796.1993
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical analysis of the gp120 surface glycoprotein of human immunodeficiency virus type 1: probing the structure of the C4 and V4 domains and the interaction of the C4 domain with the V3 loop

Abstract: We have probed the structure of the C4 and V3 domains of human immunodeficiency virus type 1 gpl20 by immunochemical techniques. Monoclonal antibodies (MAbs) recognizing an exposed gpl20 sequence, (E/ K)VGKAAMYAPP, in C4 were differentially sensitive to denaturation of gpl20, implying a conformational component to some of the epitopes. The MAbs recognizing conformation-sensitive C4 structures failed to bind to a gpl20 mutant with an alteration in the sequence of the V3 loop, and their binding to gpl20 was inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
82
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(92 citation statements)
references
References 41 publications
9
82
1
Order By: Relevance
“…Since the deletion of the V3 loop from gp120 resulted in a drastic decrease of MTCPP binding (Figs 2 and 4), the blocking effect of this compound on mAb 588D binding to gp120 can be mostly ascribed to allosteric effects resulting from MTCPP binding to the V3 loop. This explanation is consistent with the reported reciprocal allosteric interactions between the V3 loop and the CD4 binding site (McKeating et al, 1992;Pinter et al, 1993;Moore et al, 1994), between the gp120 V3 and C2 domains affecting the gp120-gp41 association (Willey and Martin, 1993;Willey et al, 1994;Stamatatos and Cheng-Mayer, 1993), between the V3 and C4 domains (Wyatt et al, 1992;Moore et al, 1993), between the V3 and VUV2 domains (Koito et al, 1994), and the observation that binding of CD4 to gp120 diminished its subsequent association with MTCPP ( Table 2).…”
Section: Discussionsupporting
confidence: 86%
“…Since the deletion of the V3 loop from gp120 resulted in a drastic decrease of MTCPP binding (Figs 2 and 4), the blocking effect of this compound on mAb 588D binding to gp120 can be mostly ascribed to allosteric effects resulting from MTCPP binding to the V3 loop. This explanation is consistent with the reported reciprocal allosteric interactions between the V3 loop and the CD4 binding site (McKeating et al, 1992;Pinter et al, 1993;Moore et al, 1994), between the gp120 V3 and C2 domains affecting the gp120-gp41 association (Willey and Martin, 1993;Willey et al, 1994;Stamatatos and Cheng-Mayer, 1993), between the V3 and C4 domains (Wyatt et al, 1992;Moore et al, 1993), between the V3 and VUV2 domains (Koito et al, 1994), and the observation that binding of CD4 to gp120 diminished its subsequent association with MTCPP ( Table 2).…”
Section: Discussionsupporting
confidence: 86%
“…Whereas the V3 loop has been described as necessary for binding to chemokine receptors (6,24), other regions of gp120 have also been implicated (10,(25)(26)(27). It has been reported that the V3 loop interacts with residues from the C4 region (28,29). Hence, changes in the conformation of the V3 loop may determine whether the residues involved in coreceptor binding from conserved regions of gp120 are in a position that allows interaction of the native molecule with particular coreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…The fourth conserved domain of gp120 (C4) has been implicated as contributing to the binding surface for CD4 (34)(35)(36). In accord with this proposal is the finding that mAbs reactive with this region inhibit the interaction between recombinant gp120 and CD4 (22) and neutralize in a group-specific manner (21)(22)(23)34). Another group of neutralizing mAbs of human origin overhps broadly with the CD4 binding domain of gp120 (24)(25)(26)(37)(38)(39)(40).…”
Section: Sllmmarymentioning
confidence: 95%
“…Neutralizing antisera and mAbs have been raised against gp120 in the form of recombinant or purified glycoprotein or synthetic peptides, or during natural infection with the virus . For many mAbs, their epitopes have been mapped by analysis of their binding to synthetic peptides (5-16, 18, 21, 22, 24), recombinant glycoproteins containing site-directed mutations (25)(26)(27), or a combination of both strategies (19,20,23). Such analyses have allowed a partial understanding of the exposure and spatial relationship of these mAb epitopes on gp120 (19,20,(22)(23)(24)(25)(26)(27)(28).…”
Section: Sllmmarymentioning
confidence: 99%